Neuroprotective Effects of Qingnao Dripping Pills Against Cerebral Ischemia via Inhibiting NLRP3 Inflammasome Signaling Pathway: In Vivo and In Vitro - Chen Fu; Xinyang Zhang; Zixiu Zeng; Yang Tian; Xianglan Jin; Fengli Wang; Zhenmin Xu; Baoxin Chen; Hong Zheng; Xuemei Liu (Frontiers Media S.A., 2020)
Ischemic stroke patients suffer from relatively limited treatment options. Studies have shown that in cerebral ischemia, NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome is a key mediator in mediating inflammatory responses and results in activation of apoptosis signaling pathways. Here we assessed the in vivo and in vitro effects of Qingnao Dripping Pills (QNDP), a traditional Chinese prescription, on inflammatory responses and apoptosis. Our results showed that QNDP could significantly decrease cerebral ischemia injury, improve neurological function and inhibit apoptosis in rats impaired by middle cerebral artery occlusion (MCAO). Further, we found that QNDP inhibited NLRP3 inflammasome expression both in MCAO rats and in SH-SY5Y cells under OGD. Moreover, the levels of inflammatory cytokines including interleukin-1β (IL-1β) and IL-18, which mediated by NLRP3 inflammasome and increased in MCAO rats, could be reduced by QNDP, suggesting that QNDP could protect the neurons against inflammation through a mechanism mediated by NLRP3 inflammasome. Nuclear factor-kappa B (NF-κB) was also involved in the anti-inflammatory effect of QNDP. In conclusion, QNDP had neuroprotective effects against cerebral ischemia via inhibiting NLRP3 inflammasome signaling pathway, and was a potential candidate for the future treatment of ischemic stroke.